Power consumption analysis using deep sleep method on NodeMCU 8266 for power efficiency in IoT system - Achmad Zuchriadi; Fajar Rahayu; Hollanda Arief Kusum; Irga Irga (Jurnal Mantik, 2024)
The Internet of Things has been implemented in various fields. The implementation of the Internet of Things is mostly carried out in remote areas that use batteries and solar panels as power sources. However, the efficiency of solar panels is still low while battery capacity is limited. For this reason, it is necessary to find a way so that an Internet of Things system only requires low power. One way is to use deep sleep mode on the microcontroller. This research was conducted by designing an IoT System for agriculture using the Nodemcu 8266 microcontroller. Furthermore, measurements of voltage, current and power consumption of the system were carried out using normal mode and deep sleep mode. Furthermore, a comparison was made between the measurement results between normal mode and deep sleep mode. Based on the measurement results, it is obtained that the voltage consumption of both normal mode and deep sleep mode results are the same, while the current consumption and power consumption of deep sleep mode are only 20% of the current consumption and power consumption of normal mode. This illustrates that deep sleep mode is more efficient in electrical power consumption, so it is very suitable for use for an IoT system implemented in remote areas